Mandatory Rest Stops Improve Athlete Safety during Event Medical Coverage for Ultramarathons. Issue 1 (11th January 2016) - Joslin, Jeremy; Mularella, Joshua; Bail, Allison; Wojcik, Susan; Cooney, Derek R.
Abstract: Introduction: Provisions of medical direction and clinical services for ultramarathons require specific attention to heat illness. Heat stress can affect athlete performance negatively, and heat accumulation without acclimatization is associated with the development of exertional heat stroke (EHS). In order to potentially mitigate the risk of this safety concern, the Jungle Marathon (Para, Brazil) instituted mandatory rest periods during the first two days of this 7-day, staged, Brazilian ultramarathon. Methods: Race records were reviewed retrospectively to determine the number of runners that suffered an emergency medical complication related to heat stress and did not finish (DNF) the race. Review of records included three years before and three years after the institution of these mandatory rest periods. Results: A total of 326 runners competed in the Jungle Marathon during the 2008-2013 period of study. During the pre-intervention years, a total of 46 athletes (21%) DNF the full race with 25 (54.3%) cases attributed to heat-related factors. During the post-intervention years, a total of 26 athletes (24.3%) DNF the full race with four (15.4%) cases attributed to heat-related factors. Conclusion: Mandatory rest stops during extreme running events in hot or tropical environments, like the Jungle Marathon, are likely to improve athlete safety and improve the heat acclimatization process. J Joslin, J Mularella, A Bail, S Wojcik, DR Cooney .Mandatory rest stops improve athlete safety during event medical coverage for ultramarathons .Prehosp Disaster Med .2016 ;31 (1 ):43 –45 .